Leukocyte Cathepsin C Deficiency Attenuates Atherosclerotic Lesion Progression by Selective Tuning of Innate and Adaptive Immune Responses. Issue 1 (January 2015) - Herías, Veronica; Biessen, Erik A.L.; Beckers, Cora; Delsing, Dianne; Liao, Mengyang; Daemen, Mat J.; Pham, Christine C.T.N.; Heeneman, Sylvia
<x xml:space="preserve">Abstract</x> Objective— The protein degrading activity of cathepsin C (CatC), combined with its role in leukocyte granule activation, suggests a contribution of this cystein protease in atherosclerosis. However, no experimental data are available to validate this concept. Approach and Results— CatC gene and protein expression were increased in ruptured versus advanced stable human carotid artery lesions. To assess causal involvement of CatC in plaque progression and stability, we generated LDLr−/−//CatC−/− chimeras by bone marrow transplantation. CatC−/− chimeras presented attenuated plaque burden in carotids, descending aorta, aortic arch and root, at both the early and advanced plaque stage. CatC was abundantly expressed by plaque macrophages and foam cells. CatC expression and activity were dramatically downregulated in plaques of CatC−/− chimeras, supporting a hematopoietic origin of plaque CatC. Our studies unveiled an unexpected feedback of CatC deficiency on macrophage activation programs and T helper cell differentiation in as much as that CatC expression was upregulated in M1 macrophages, whereas its deficiency led to combined M2 (in vitro) and Th2 polarization (in vivo). Conclusions— Our data implicate CatC has a role in the selective tuning of innate and adaptive immune responses, relevant to a chronic immune disease, such as atherosclerosis.